A Model to Identify Candidates for Lymph Node Dissection Among Patients With High-Risk Endometrial Endometrioid Carcinoma According to Mayo Criteria - Lu, Wen; Chen, Xiaoyue; Ni, Jingyi; Li, Zhen; Su, Tao; Li, Shuangdi; Wan, Xiaoping (Frontiers in Oncology, 2022)
Abstract Background: The Mayo criteria are the most widely accepted algorithm for predicting the risk of lymph node metastasis in endometrial endometrioid carcinoma (EEC), However, the clinical value of these criteria in high-risk patients is limited and inconclusive. Methods: 240 patients with EEC meeting the Mayo high-risk criteria between January 1, 2015, and December 31, 2018, were included in our study. We retrospectively collected the laboratory reports, basic clinical information, clinicopathologic, and IHC findings, as well as the sequences of molecular pathological markers of these patients. A nomogram for predicting the likelihood of positive lymph node status was established based on these parameters. Results: Among the 240 patients, 17 were diagnosed with lymph node metastasis. The univariable analyses identified myometrial invasion >50%, aberrant p53 expression, MSI and CA125 ≥35U/ml as potential risk factors for lymph node metastasis. The multivariable analyses showed that aberrant p53 expression, MSI and CA125 ≥35 U/ml were independent predictors of lymph node metastasis. The AUC for the nomogram was 0.870, as compared to 0.665 for the Mayo criteria. Conclusions: Our novel prediction model effectively identifies patients at high risk for lymphatic metastasis. This model is a promising strategy for personalized surgery in patients with high risk according to the Mayo criteria.